RELIGIOUS TRADITIONS AND SOCIAL BEHAVIOR IN NATIONAL CULTURE: ANALYSIS OF CULTURAL TRANSMISSION, VALUES AND NORMATIVE PRACTICES (International Congress on Economics, Management and Business Studies, 2026)
This scientific article analyzes the formation, transmission and role of religious traditions in the framework of national culture and the regulation of social behavior at the intersection of cultural studies and sociological approaches. In the study, religious traditions are interpreted not only as a set of religious practices, but also as a cultural mechanism that legitimizes social norms in the consciousness of society and directs everyday behavior. According to the author's position, religious traditions form stable models of moral criteria, social responsibility and collective behavior in national culture, but their influence in modern society is not uniform and unidirectional. The article examines the influence of religious traditions on social behavior in a historical, cultural and discursive context, and their transformation and modern interpretations are problematized. The results of the study justify the need to understand religious traditions not as a static layer of culture, but as a dynamic phenomenon that constantly reshapes social behavior.
Keywords: national culture, religious traditions, social behavior, cultural norms, moral values, religious identity, cultural transmission.